Climate-induced surface water variability at Monte San Nicola type-section (Sicily, southern Italy): New data across the Gelasian GSSP - Addante, Marina; Maiorano, Patrizia; Scopelliti, Giovanna; Girone, Angela; Marino, Maria; Trotta, Samanta; Caruso, Antonio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)
We present the first high-resolution results on planktonic foraminiferal stable oxygen isotopes and calcareous plankton assemblages at the Monte San Nicola GSSP section (near Gela, Sicily), the type-section for the Lower Pleistocene Gelasian Stage. The oxygen isotope profile is remarkably similar to the Eastern Mediterranean ox-ygen isotope record and indicates that the studied section, extending from marine isotope stage (MIS) G4 to MIS 103, clearly records glacial-interglacial variability. Cyclic changes of calcareous plankton assemblages (calcareous nannofossils and foraminifera) indicate that warmer and stratified surface waters occurred during interglacials, while cooler and unstable conditions developed during glacial phases. Signatures of further increase in surface water stratification are also captured by our surface water proxies and are coeval with enhanced monsoon run-off, developed during precession minima/insolation maxima. The surface water changes recorded at the Monte San Nicola section are in phase with North Atlantic climate variability, even at suborbital scale, and reveal evidence of the first significant southward migration of the Subarctic Front in the mid-latitudes during MIS 104, slightly below the GSSP. The overall dataset provides precise alignment of the Gelasian GSSP within MIS 103 as well as new climatostratigraphic constraints, close to the GSSP, thus improving its correlation potential outside the type-area.